Synergistic role of Foliar-Applied Nano-Fertilizer enhances drought tolerance in cluster bean (Cyamopsis tetragonoloba L.) - Javaria Munir; Muhammad Nazim; Nadia Jabeen; Muqarrab Ali; Anis Ali Shah; Haider Sultan (Plant Nano Biology)
Drought stress during the reproductive stage critically reduces the productivity of cluster bean (Cyamopsis tetragonoloba L.) in arid regions. This study evaluated the effectiveness of foliar-applied nano-fertilizers as a sustainable strategy to improve drought tolerance and maintain cluser bean yield. A field experiment was conducted in June 2022 at MNS-University of Agriculture, Multan, Pakistan, using two genotypes (BR-2017 and BR-2021) under different irrigation regimes. Treatments included nano-Potassium (2470 gm/ha), nano-Zinc (1235 gm/ha), nano-Boron (930 gm/ha), and their combined application (825, 415, and 310 gm/ha, respectively). The experiment followed a split-plot RCBD design with three replications. BR-2021 showed superior performance, especially with the combined nano-fertilizer treatment, resulting in notable increases in plant height (30.3 %), pods per plant (1.5 %), pod yield (7.31 %), 100-seed weight (12.4 %), photosynthetic rate (4.44 %), and protein content (7.34 %) compared to the skipped irrigation with control. Under water deficit, K, Zn, and B nano-fertilizers improved photosynthesis rate by 7.12 %, 13.2 %, and 16.34 % in BR-2021 and by 39.2 %, 37.4 %, and 40.3 % in BR-2017, respectively. Transpiration rates also increased slightly across treatments. Overall, BR-2021 showed better performance than BR-2017 in key agronomic and physiological parameters. These findings revealed that the potential of nano-fertilizers as an eco-friendly and effective tool for enhancing drought resilience and sustaining cluster bean productivity under limited water availability, thereby contributing to climate-resilient and resource-efficient agriculture.